The effect of homocysteine on the expression of CD36, PPARγ, and C/EBPα in adipose tissue of normal and obese mice. (3rd September 2021) - Mentese, Ahmet; Dogramaci, Seniz; Demir, Selim; Yaman, Serap Ozer; Ince, Imran; Altay, Diler Us; Erdem, Mehmet; Turan, Ibrahim; Alver, Ahmet
Abstract: The purpose of this study was to investigate the effect of homocysteine (Hcy) on CD36, PPARγ, and C/EBPα gene and protein expression in adipose tissue obtained from normal and high-calorie diet obesity models. CD36, PPARγ, and C/EBPα gene expression and protein levels in adipose tissue specimens were determined using the RT-PCR and ELISA methods, respectively. Significantly increased CD36 gene expression was observed in adipose tissue from obese mice, while Hcy significantly reduced CD36 gene expression in adipose tissue from normal and obese mice. PPARγ and C/EBPα gene expression levels decreased significantly in all groups compared to the normal group. In addition, levels of both PPARγ and C/EBPα gene expression were lower with Hcy supplementation compared to their own controls. In conclusion, Hcy's reduction of CD36 gene expression in adipose tissue may be one probable factor in hyperhomocysteinemia representing an independent risk factor for cardiovascular diseases.